2005
DOI: 10.4081/monaldi.2005.658
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolitis Obliterans Organising Pneumonia (BOOP) in a lung cancer patient after lobectomy

Abstract: A 79 year-old patient with lung cancer underwent a standard thoracotomy and lobectomy. Postoperatively, he developed low-grade fever and dyspnoea. Chest X-rays showed progressive lung infiltrates, which was subsequently diagnosed to be Bronchiolitis Obliterans Organizing Pneumonia (BOOP) by transbronchial lung biopsy. He responded well to corticosteroid therapy. The case report is followed by a brief discussion on BOOP in association with lung cancer and thoracotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, in this group of patients OP was diagnosed after chemo-or radiotherapy. Sanchez et al found OP in the opposite lung of patients with adenocarcinoma, and Yan et al described a patient with squamous cancer treated by surgery who developed OP after this procedure [9,10]. Also Song et al published a case of OP in the course of bronchoalveolar carcinoma [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, in this group of patients OP was diagnosed after chemo-or radiotherapy. Sanchez et al found OP in the opposite lung of patients with adenocarcinoma, and Yan et al described a patient with squamous cancer treated by surgery who developed OP after this procedure [9,10]. Also Song et al published a case of OP in the course of bronchoalveolar carcinoma [11].…”
Section: Discussionmentioning
confidence: 99%